Helium Tribology of Inconel 617 at Elevated Temperatures up to 950°C: Parametric Study. (2nd September 2019) - Rahman, Md Saifur; Ding, Jie; Beheshti, Ali; Zhang, Xinghang; Polycarpou, Andreas A.
Abstract: This study investigates the friction and wear behavior of Inconel 617, one of the primary candidate materials for high-temperature gas-cooled nuclear reactors. Using a custom-built, high-temperature tribometer, a helium (He)-cooled reactor environment was simulated up to 950°C. To obtain a comprehensive understanding of the Inconel 617 tribological response, the effects of contact load, temperature, air and He environments, sliding speed, and sliding distance were studied. From the conditions investigated, the coefficient of friction and wear values are the highest in a high-temperature He atmosphere. Scanning electron microscopy, energy dispersive spectroscopy, and X-ray diffraction techniques were used to analyze the Inconel 617 oxide layer. Analysis of the samples tested in the He atmosphere showed the presence of Cr-rich oxide with a lower presence of Co-Ni-Mo compared to the samples tested in air. Characterization also revealed the existence of a very hard protective glaze layer in air while such layer was not observed in the He environment, which was associated with higher wear/friction values.